Membrane vesicle secretion and prophage induction in multidrug‐resistant Stenotrophomonas maltophilia in response to ciprofloxacin stress - Simon Devos; Wouter Van Putte; Jolien Vitse; Gonzalez Van Driessche; Stephan Stremersch; Wim Van Den Broek; Koen Raemdonck; Kevin Braeckmans; Henning Stahlberg; Misha Kudryashev; Savvas N. Savvides; Bart Devreese (Environmental Microbiology, 2017)
Summary Several bacterial species produce membrane vesicles (MVs) in response to antibiotic stress. However, the biogenesis and role of MVs in bacterial antibiotic resistance mechanisms have remained unclear. Here, we studied the effect of the fluoroquinolone ciprofloxacin on MV secretion by Stenotrophomonas maltophilia using a combination of electron microscopy and proteomic approaches. We found that in addition to the classical outer membrane vesicles (OMV), ciprofloxacin‐stimulated cultures produced larger vesicles containing both outer and inner membranes termed outer‐inner membrane vesicles (OIMV), and that such MVs are enriched with cytosolic proteins. Remarkably, OIMV were found to be decorated with filamentous structures identified as fimbriae. In addition, ciprofloxacin stress leads to the release of bacteriophages and phage tail‐like particles. Prophage induction by ciprofloxacin has been linked to pathogenesis and horizontal gene transfer in several bacterial species. Together, our findings show that ciprofloxacin treatment of S. maltophilia leads to the secretion of a heterogeneous pool of MVs and the induction of prophages that are potentially involved in adverse side‐effects during antibiotic treatment.